Multilingualism and Language Ideologies in Post-Decentralization Indonesia: Implications for Language-in-Education Policy - Mataraw, Maria Kewa; Adriansyah, Hendri (Jurnal Tahuri, 2023)
This study investigates the interplay between multilingualism and language ideologies in post-decentralization Indonesia, focusing on how local autonomy shapes language-in-education policies and practices in Nusa Tenggara Barat (NTB). It examines how teachers, students, and administrators negotiate the meanings and functions of Bahasa Indonesia, English, Arabic, and local languages, Bahasa Sasak, Bahasa Samawa, and Bahasa Mbojo, within diverse school settings. Using a qualitative multi-site case study that combines critical ethnography and language policy ethnography, the research was conducted across a junior high school, a senior high school, and a Madrasah Aliyah. Data were gathered through interviews, focus group discussions, classroom observations, and policy document analysis. Findings reveal that multilingual practices in NTB schools are structured by hierarchical ideologies in which Bahasa Indonesia and English represent academic and economic capital, Arabic symbolizes religious authority, and local languages are symbolically acknowledged yet marginalized. Although decentralization grants limited autonomy, policy implementation remains ideologically centralized. Teachers and students navigate these hierarchies ambivalently, balancing local identity with dominant discourses of modernity. The study introduces the Ideological Ecology of Multilingual Education (IEME) Framework, conceptualizing schools as ideological ecosystems where global, national, and local linguistic values intersect. It advances critical sociolinguistic theory and offers policy insights toward inclusive, context-sensitive multilingual education in postcolonial Indonesia.